Aid and the Supply Side : Public Investment, Export Performance, and Dutch Disease in Low-Income Countries - Adam, Christopher S. (Oxford University Press on behalf of the World Bank, 2013)
Contemporary policy debates on the macroeconomics of aid often concentrate on short-run Dutch disease effects, ignoring the possible supply-side impact of aid financed public expenditure. In the simple model of aid and public expenditure presented here, public infrastructure generates an inter-temporal productivity spillover, which may exhibit a sector-specific bias. The model also provides for a learning-by-doing externality, through which total factor productivity in the tradable sector is an increasing function of past export volumes. An extended computable version of this model is used to simulate the effect of a step increase in net aid flows. The simulations show that beyond the short run, when conventional demand-side Dutch disease effects are present, the relationship between enhanced aid flows and real exchange rates, output growth, and welfare is less straightforward than simple models of aid suggest. Public infrastructure investment that generates a productivity bias in favor of non-tradable production delivers the largest aggregate return to aid, but at the cost of deterioration in the income distribution. Income gains accrue predominantly to skilled and unskilled urban households, leaving the rural poor relatively worse off. Under plausible parameterizations of the model, the rural poor may also be worse off in absolute terms.